After the Storm: Inter-disciplinary Dialogic Discourses With a Post-Fishing Community - Stephenson, Carol; MacPherson, Fiona (Frontiers in Sociology, 2020)
This paper is a critical evaluation of a unique cross-disciplinary approach to working with traumatised communities which involved inter-disciplinary collaboration between an Applied Theatre director and a Sociologist. The application of the approach in a post-industrial community provides the case study basis for the evaluation. Between 2014 and 2017 community participants from Eyemouth in south east Scotland worked with an applied theatre director and a Sociologist to develop a creative performance which examined the events of the town’s fishing disaster of 1881. The Eyemouth project was facilitated through dialogic discourses between community participants, applied theatre director and sociologist in which the equalization of relationships, meaning making and active listening were established as shared values and processes. The aim of the paper is threefold. To critically address the degree to which the approach as able to: facilitate a critical evaluation of the practices of applied theatre; make visible otherwise unrecorded sociological insights as a result of the observation and interrogation of the creative performance of shared industrial heritage; facilitate public sociology that supported social activism within a disadvantaged community. Sociological observation of the creative process and its negotiation revealed previously hidden and nuanced social interactions which were then examined in discussion with the director and in focus group discussions with community participants. The creative process revealed insights into the nature and potential of post-industrial communities and enabled public sociology discourse which prompted social activism within the case study community. The approach is labour intensive and time-consuming. It demands high levels of commitment to the shared values associated with dialogic discourses on the part of both community participants and professionals. Despite this, the paper concludes that the approach could be reproduced in other settings and was successful in both facilitating the critical appraisal of AT practice and was effective as a strategy for research with, and empowerment of, disadvantaged and traumatized communities.